Eye tracking communication devices in amyotrophic lateral sclerosis: Impact on disability and quality of life. Issue 7 (December 2013) - Caligari, Marco; Godi, Marco; Guglielmetti, Simone; Franchignoni, Franco; Nardone, Antonio
Abstract: People with amyotrophic lateral sclerosis (PwALS) show progressive loss of voluntary muscle strength. In advanced disease, motor and phonatory impairments seriously hinder the patient's interpersonal communication. High-tech devices such as eye tracking communication devices (ETCDs) are used to aid communication in the later stages of ALS. We sought to evaluate the effect of ETCDs on patient disability, quality of life (QoL), and user satisfaction, in a group of 35 regular ETCD users in late-stage ALS with tetraplegia and anarthria. The following scales were administered: 1) the Individually Prioritized Problem Assessment (IPPA) scale, in three conditions: without device, with ETCD and, when applicable, with an Eye Transfer (ETRAN) board; 2) the Psychosocial Impact of Assistive Devices Scale (PIADS); and 3) the Quebec User Evaluation of Satisfaction with Assistive Technology (QUEST 2.0). With ETRAN, IPPA showed an increase in communicative abilities with respect to the condition without device, but ETCD produced a further significant increase. PIADS evidenced a large increase of QoL, and QUEST 2.0 showed high user satisfaction with ETCD use. In conclusion, ETCDs should be considered in late-stage ALS with tetraplegia and anarthria, since in these patients they can reduce communication disability and improve QoL.